Comparative Study of Pulmonary Combined Large-Cell Neuroendocrine Carcinoma and Combined Small-Cell Carcinoma in Surgically Resected High-Grade Neuroendocrine Tumors of the Lung - Wang, Yanan; Qian, Fangfei; Chen, Ya; Yang, Zhengyu; Hu, Minjuan; Lu, Jun; Zhang, Yanwei; Zhang, Wei; Cheng, Lei; Han, Baohui (Frontiers in Oncology, 2021)
Objectives Pulmonary large cell neuroendocrine carcinoma (LCNEC) and small cell lung cancer (SCLC) are both classified as pure and combined subtypes. Due to the low incidence and difficult diagnosis of combined LCNEC(C-LCNEC) and combined SCLC(C-SCLC), few studies have compared their clinical features and prognosis. Materials and Methods We compared the clinical features, mutation status of driver genes (EGFR, ALK, ROS1, KRAS and BRAF) and prognosis between C-LCNEC and C-SCLC. Univariate and multivariate Cox regression analysis were applied for survival analysis. Results We included a total of 116 patients with C-LCNEC and 76 patients with C-SCLC in the present study. There were significant differences in distribution of smoking history, tumor location, pT stage, pN stage, pTNM stage, visceral pleural invasion (VPI) and combined components between C-LCNEC and C-SCLC (P<0.05 for all). C-SCLC was more advanced at diagnosis as compared to C-LCNEC. The incidence of EGFR mutations in C-LCNEC patients was higher than C-SCLC patients (25.7% vs. 5%, P=0.004). We found that tumor size, pN stage, peripheral CEA level and adjuvant chemotherapy were independently prognostic factors for DFS and OS in C-LCNEC patients, while peripheral NSE level, pT stage, pN stage, VPI and adjuvant chemotherapy were independently associated with DFS and OS for C-SCLC patients (P<0.05 for all). Propensity score matching with adjustment for the confounders confirmed a more favorable DFS (P=0.032) and OS (P=0.019) in patients with C-LCNEC in comparison with C-SCLC patients upon survival analysis. Conclusions The mutation landscape of driver genes seemed to act in different way between C-SCLC and C-LCNEC, likely by which result in clinical phenotype difference as well as better outcome in C-LCNEC.